Elevated ozone and nitrogen deposition affect nitrogen pools of subalpine grassland. (June 2015) - Bassin, Seraina; Käch, David; Valsangiacomo, Alain; Mayer, Jochen; Oberholzer, Hans-Rudolf; Volk, Matthias; Fuhrer, Jürg
Abstract: In a free-air fumigation experiment with subalpine grassland, we studied long-term effects of elevated ozone (O3 ) and nitrogen (N) deposition on ecosystem N pools and on the fate of anthropogenic N. At three times during the seventh year of exposure, N pools and recovery of a stable isotope tracer ( 15 N) were determined in above- and belowground plant parts, and in the soil. Plants were much better competitors for 15 N than soil microorganisms. Plant N pools increased by 30–40% after N addition, while soil pools remained unaffected, suggesting that most of the extra N was taken up and stored in plant biomass, thus preventing the ecosystem from acquiring characteristics of eutrophication. Elevated O3 caused an increase of N in microbial biomass and in stabilized soil N, probably resulting from increased litter input and lower litter quality. Different from individual effects, the interaction between the pollutants remained partly unexplained. Highlights: O3  × N effects on subalpine grassland were studied in a free-air fumigation experiment. Plants were best competitors for N and they accumulated most of the extra N. Elevated O3 increased the stabilized soil N pool by altering litter quantity and quality. Interactions between O3 and N were observed but remained partly unexplained. Abstract : In subalpine grassland, N from increased N deposition accumulated in plants, while elevated O3 increased the soil N pool by altering litter quantity and quality.